Inclusive Leadership in Enhancing Teacher Performance in Digital Transformation Era - Dewi, Retno Kusumo; Pramono, Suwito Eko; Wahyudin, Agus (Universitas Negeri Semarang, 2025)
The era of digital transformation has brought major changes to the world of education, including in the learning system, teaching process, and the use of digital technology in schools. Although it is expected that there will be an increase in teacher performance, various challenges are still faced, such as limited digital competence, gaps in access to technology, and low student achievement in international assessments. This study aims to examine the role of inclusive leadership in improving teacher performance in responding to the challenges of the Digital Transformation Era. Using a qualitative descriptive approach with a literature study method, this study analyzes various scientific publications that focus on inclusive leadership, teacher performance, and digital transformation in education. The results of the study show that inclusive leadership, which is characterized by openness, empathy, and collaboration, is able to create a supportive and adaptive work environment, empower teachers, strengthen digital literacy, and encourage learning innovation. Inclusive leaders are able to understand the diversity of teacher readiness, provide space for professional development, and create a sense of psychological safety. In conclusion, inclusive leadership is an effective strategy in improving teacher performance in the era of digital transformation, which has an impact on the quality of teaching and student learning outcomes.